2016
DOI: 10.1007/s12035-016-0333-1
|View full text |Cite|
|
Sign up to set email alerts
|

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis

Abstract: Myelin-associated inhibitors, such as NogoA, myelin-associated glycoprotein (MAG), and oligodendrocyte myelin glycoprotein (OMgp), play a pivotal role in the lack of neuroregeneration in multiple sclerosis, an inflammatory demyelinating disease of the central nervous system (CNS). Matrine (MAT), a monomer that is used in traditional Chinese medicine as an anti-inflammatory agent, has shown beneficial effects in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. However, the underlying mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 48 publications
0
15
0
1
Order By: Relevance
“…Matrine, which was approved by Chinese FDA (CFDA) in 1995, is derived primarily from Sophora species plants and has a chemical formula of C 15 H 24 N 2 O (5). Matrine exhibits a wide range of pharmacological effects and has long been applied to treat viral hepatitis (6), neuropathic pain (7), isoproterenol-induced cardiotoxicity inflammatory and other diseases (8,9). In addition, increasing evidence has revealed that matrine displays anticancer effects in various cancers, such as gastric (10), rhabdomyosarcoma (11), acute myeloid leukemia (12), osteosarcoma (13), prostate (14), breast (15) and lung cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…Matrine, which was approved by Chinese FDA (CFDA) in 1995, is derived primarily from Sophora species plants and has a chemical formula of C 15 H 24 N 2 O (5). Matrine exhibits a wide range of pharmacological effects and has long been applied to treat viral hepatitis (6), neuropathic pain (7), isoproterenol-induced cardiotoxicity inflammatory and other diseases (8,9). In addition, increasing evidence has revealed that matrine displays anticancer effects in various cancers, such as gastric (10), rhabdomyosarcoma (11), acute myeloid leukemia (12), osteosarcoma (13), prostate (14), breast (15) and lung cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our study demonstrates that MAT effectively suppresses CNS in ammation, demyelination and axonal loss in optic nerves, as well as RGC apoptosis in experimental ON. The mechanisms underlying these effects may include: 1) its anti-in ammatory effects (18,19,38); 2) the potential to promote production of neurotrophic factors, such as NGF and BDNF, as previously reported (14,15). These effects, together, could convert a hostile environment into a supportive one for neural cells, thus reducing myelin and axonal damage of the optic nerve and protecting RGCs from apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…Matrine (MAT), a natural quinolizidine alkaloid compound extracted from the herb root of Sophorae avescens, with a molecular weight (MW) of 258.43 (C 15 H 24 N 2 O) (14)(15)(16), is known for its various effects in animal models of EAE, including protection against apoptosis, tumor and brotic tissue development, and in ammation (17). We have recently shown that MAT can ameliorate clinical signs and alleviate neuro-axonal injury in the CNS of EAE animals by regulatory T cells, reducing Th1 and Th17 cells in the CNS and periphery and increasing the number of neural protective molecules (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Natural compounds and their derivatives have become an important source of new MS therapies [7,14,20]. The dry root of Astragalus membranaceus (commonly known as Huang Qi) is one of the most commonly used Chinese traditional medicines for its multitude of beneficial effects that include liver protection, anti-aging, anti-stress, and has been used to treat immune-related diseases [13,15,31].…”
Section: Introductionmentioning
confidence: 99%